Inter-linkages and causal relationships between US and BRIC equity markets: An empirical investigation - Amanjot Singh; Manjit Singh (Arab Economic and Business Journal, 2016)
The US and BRIC economies are sharing increasing trade as well as financial linkages since the last decade. In this regard, the present study attempts to capture long run and short run inter-linkages and causal relationships between the US and BRIC equity markets during different time frames, i.e., pre-crisis, crisis and post-crisis periods. The study employs Johansen cointegration, VAR, VECM, Toda-Yamamoto's Granger causality, generalized impulse responses, and variance decomposition models to account for the said linkages. For the full sample period analysis, Gregory-Hansen cointegration and Diebold and Yilmaz's (2011) spillover index approaches are also employed. Overall, the results report changing market dynamics and partial integration across the years 2004-2014.
Keywords: 330; Causal relationships; BRIC; Equity markets; Inter-linkages; US